Definición de nanomateriales para Colombia (2016)
Due to the increasing production and use of nanomaterials in research and development activities in Colombia, it is necessary to define the nanomaterial term in order to facilitate decision-making process regarding initiatives with a regulatory or normative character. This article presents the nanomaterials definition that has been adopted by the National Advisory Council for Nanoscience and Nanotechnology, a Colombian Network of Nanoscience and Nanotechnology. © 2016, Universidad Nacional de Colombia. All rights reserved.